2000
DOI: 10.1144/gsl.sp.2000.170.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic evolution, 40 Ar- 39 Ar chronology and tectonic model for the Neelum valley, Azad Kashmir, NE Pakistan

Abstract: This paper describes the geology, tectonometamorphic history and geochronology of part of the northern flank of the Neelum valley in Azad Kashmir, NE Pakistan. Metamorphic crystalline rocks in this area belong to the Lesser and Higher Himalayan Crystalline complexes. Geological mapping of about 1500 km2 confirms the presence of three main tectonic units characterized by similar lithostratigraphic sequences but with different tectonometamorphic histories. Whether these tectonic units belong to the Lesser or Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Major rivers and their tributaries in the Kaghan Valley (River Kunhar) and in the Neelum Valley (River Neelum) and two major lakes (Lake Lulusar and Lake Saif‐ul‐Muluk) are also shown. Modified after Wadia (), Chaudhry and Ghazanfar (), Greco et al (), Greco and Spencer (1993), Fontan, Schouppe, Hunziker, Martinpotti, and Verkaeren (), Kaneko et al (), O'Brien, Zotov, Law, Khan, and Jan (), Rehman et al () and references therein…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Major rivers and their tributaries in the Kaghan Valley (River Kunhar) and in the Neelum Valley (River Neelum) and two major lakes (Lake Lulusar and Lake Saif‐ul‐Muluk) are also shown. Modified after Wadia (), Chaudhry and Ghazanfar (), Greco et al (), Greco and Spencer (1993), Fontan, Schouppe, Hunziker, Martinpotti, and Verkaeren (), Kaneko et al (), O'Brien, Zotov, Law, Khan, and Jan (), Rehman et al () and references therein…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Tertiary-aged UHP eclogites have been described from North Pakistan (Pognante & Spencer 1991;Fontan et al 2000;O'Brien et al 2001) and northern India (Guillot et al 1997). In the NW Himalaya, collision between continental India and the Kohistan island arc (the last exotic block to be accreted to continental Asia) is interpreted as having occurred at between 50 and 55 Ma (see discussions by Rowley (1996) and Treloar (1997)).…”
Section: Geological Settingmentioning
confidence: 99%
“…Cooling through 500 8C after this early Tertiary metamorphism was complete by c. 40 Ma (Treloar & Rex 1990;Chamberlain et al 1991;Tonarini et al 1993). The eclogite-facies rocks described from the Kaghan and Neelum valleys in Pakistan (Pognante & Spencer 1991;Fontan et al 2000;O'Brien et al 2001) lie in the most northerly exposed parts of the Indian Plate on the immediate footwall of the Main Mantle Thrust, which separates the Indian Plate rocks from the overriding Kohistan arc. Treloar (1997) suggested that, during early stages of their exhumation, the UHP rocks were thrust upon the amphibolitefacies rocks of the Indian Plate.…”
Section: Geological Settingmentioning
confidence: 99%
“…1), were found at the end of the 1980s in the Kaghan Valley, NE Pakistan (Spencer et al. , 1990; Pognante & Spencer, 1991) and of the adjoining Neelum Valley (Fontan et al. , 2000) (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Eclogites, in particular, first discovered by Berthelsen (1953) as boudinaged dykes in the granitic orthogneiss of the Tso Morari dome, eastern Ladakh (Fig. 1), were found at the end of the 1980s in the Kaghan Valley, NE Pakistan (Spencer et al, 1990;Pognante & Spencer, 1991) and of the adjoining Neelum Valley (Fontan et al, 2000) (Fig. 1), whereas granulitized and amphibolitized eclogites were discovered in the Eastern Himalaya Parkinson & Kohn, 2002).…”
Section: Introductionmentioning
confidence: 99%